# Taylor Series

## Homework Statement

Write the Taylor series of the function f(x) = ($$\pi$$ -x)^-2 around a = 0

## Homework Equations

($$\pi$$ - x)^-2 = f(a) + f'(a)(x-a) + [f''(a)(x-a)^2]/(2!) +......+ [f^n(a)(x-a)^n]/(n!)

## The Attempt at a Solution

This is what i have and i am not sure i am showing it correctly or compleatly.

f(x) = ($$\pi$$ -x)^-2
f'(x) = 2($$\pi$$ - x)^-3
f''(x) = 6($$\pi$$ - x)^-4
f'''(x) = 24($$\pi$$ - x)^-5

($$\pi$$ - x)^-2 = f(a) + [f'(a)(x-a)^2]/(2!) +......+ [f^n(a)(x-a)^n]/(n!)

= ($$\pi$$-0)^-2 + [(2($$\pi$$-0)^-3)(x-0)^2]/(2!) + [(6($$\pi$$-0)^-4)(x-0)^3]/(3!) + ......

= $$\pi$$^-2 + 2($$\pi$$^-3)x +[6($$\pi$$^-4)(x^2)]/(2!) + [24($$\pi$$^-5)(x^3)]/(3!) + ........

Last edited:

Related Calculus and Beyond Homework Help News on Phys.org
You seem to have written the series wrong: where is the f(a) term? And why isn't the f'(a) term multiplied by (x-a)? Your derivatives are correct, now you just need to substitute into the (correct) series that you wrote in the "relevant equations" section...

You seem to have written the series wrong: where is the f(a) term? And why isn't the f'(a) term multiplied by (x-a)? Your derivatives are correct, now you just need to substitute into the (correct) series that you wrote in the "relevant equations" section...
I looked over my work again and found where i messed up, thanks.
the final answer i get is:

($$\pi$$-x)^-2 = $$\pi$$^-2 + 2($$\pi$$^-3)(x) + 3($$\pi$$^-4)(x^2) +....